Hydro-plastic response of beams and stiffened panels subjected to extreme water slamming at small impact angles, Part I: An analytical solution. (May 2019) - Yu, Zhaolong; Amdahl, Jørgen; Greco, Marilena; Xu, Huili
Abstract: Water impact (slamming) is a strongly nonlinear phenomenon including significant fluid structure interactions. In the case of slamming with a small impact angle between the structure and water, the coupling between hydrodynamic pressure and the elastic responses of structures, known as hydroelasticity, matters. This has been studied extensively. However, when structures are subjected to violent water slamming in extreme sea states, large stresses may occur that exceed the material yield stress, causing large plastic flow and permanent damage. In such cases, the plastic responses of a structure will be strongly coupled with the hydrodynamic pressure, termed as hydro-plasticity. Hydro-plastic slamming has rarely been studied before. This is Part I of a two-part companion paper. The paper advances the state-of-the-art of hydro-plastic slamming by formulating, for the first time, an analytical model coupling the hydrodynamic forces and the plastic response of rectangular beams and one-way stiffened panels. The studied scenarios are flat or nearly flat water impacts, which are critical for hydro-plasticity excitation. The impact angle between the water free surface and the structure should preferably be no larger than 5°. Based on the proposed model, the governing non-dimensional parameters for hydro-plastic slamming are identified and discussed. Design curves for plate strips and stiffened panels against extreme slamming are developed. Part II- Numerical verification and analysis presents numerical verification and discussion of the analytical model by comparing with results from the multi-material Arbitrary Lagrangian Eulerian (ALE) simulations. The proposed analytical model does not require the challenging estimation of pressure history that is normally used in the design against slamming. Only the initial impact velocity is needed as the main input. The resulting non-dimensional curves may be utilized in rules and standards for the design of ships and offshore structures against extreme slamming loads. Highlights: An analytical model is proposed for the hydro-plastic response of beams and stiffened panels subjected to extreme water slamming at small impact angles. The model well captures the coupling between the hydrodynamic pressure and large plastic deformations of the structures during slamming. The travelling-hinge concept is used for the plastic structural response. A non-dimensional velocity parameter is identified and is found to govern the hydro-plastic slamming phenomenon. Design curves are recommended for beams and stiffened panels against extreme water slamming.